Towards Autonomous MAV Soaring in Cities: CFD Simulation, EFD Measurement and Flight Trials. Issue 4 (December 2015) - Watkins, Simon; Mohamed, Abdulghani; Fisher, Alex; Clothier, Reece; Carrese, Robert; Fletcher, David F.
MAVs are increasingly being used in complex terrains, such as cities, despite challenges from the highly turbulent flow fields. We investigate the flow around a nominally cuboid building of height 40m both computationally and experimentally in a 1/100th scale wind-tunnel test. A relatively new computational technique, Improved Delayed Detached Eddy Simulation (IDDES), was used for computing the time-varying flow around the building and surrounding domain. The atmospheric boundary layer velocity and turbulent intensity profiles were replicated at the inlet boundary of the computational domain and wind tunnel. The spatial flow field from the CFD was investigated for locating suitable areas of lift, in order to see if soaring flight would be feasible. Good agreement was found with the wind-tunnel results. Flight trials of a small flying wing aircraft were conducted from the roof demonstrating the possibility of keeping aloft with no conventional power system. Soaring was achieved under piloted control and autonomously. The CFD results proved useful in locating the best lift areas and provided insights into path planning.